Model Pembelajaran Hukum Acara Pidana Berbasis Bedah Perkara dalam Mendukung Program Merdeka Belajar Kampus Merdeka (MBKM) - Mhd Teguh Syuhada Lubis; Ismail Koto (Mahesa Research Center, 2022)
The purpose of this research is to develop a learning model in criminal procedure law courses where so far lecturers have only used conventional methods or patterns which have actually become obstacles faced by students in absorbing lecture material because these methods or patterns are considered no longer effective to be applied. , students must be given an interesting method or learning model as a way for students to master the lecture material in the Criminal Procedure Law course. The procedure used to collect data in this study is in the form of documentation, namely guidelines used in the form of notes or quotes, searching for legal literature, books and others related to the identification of problems in this study both offline and online. This study concludes that in teaching and learning activities, the subject of criminal procedure law is one of the mandatory courses for law faculty students as a basis for knowing the basics of Indonesian criminal procedure law so that they can then know the criminal procedure law system that applies in Indonesia. criminal procedure law, as well as outlining the elements of criminal procedure. The difficulty of providing an understanding of the subject matter of the Criminal Procedure Law course and in particular the difficulty of students digesting the subject matter of the Criminal Procedure Law is the most important part to innovate and renew the learning model in this Criminal Procedure Law course, so the renewal model offered is the surgical-based Learning Model. criminal proceedings as a way to support the Merdeka program to study an independent campus.